Entrepreneurial Energy and Opportunities Existing in Space - Leong, David (Journal of Entrepreneurship, Business and Economics, 2021)
The space within which the entrepreneurs exist is filled with risks, opportunities and other environmental resources. Scholars have argued that entrepreneurs are constantly discovering and identifying value potentials because significant values arise from the existence of positive externalities which can be captured and exploited. Positive externalities or opportunities can create substantial and desirable gains if they can be monetized, leveraged and exploited. These externalities refer to the natural environmental resources within the space where the entrepreneurs operate. From the perspective of space, this paper will explore the emergence of opportunities or risks within the space through the theoretical lens of structuration and complex science and will, specifically, discuss the collision and the meeting of opportunities with the entrepreneurs at the nexus from the perspective of entrepreneurial energy excitation. Entrepreneurship originates from a nexus of individuals and opportunities. The unique juncture in space or nexus in which the entrepreneurs and opportunities exist is central to the study of entrepreneurship because it is in this juncture or nexus that identification and evaluation of risks and opportunities take place. It is the subsequent human actions, driven by the level of entrepreneurial energy that will lead to the myriad of possible venture pathways. For risks, entrepreneurs perceive them and will subsequently work towards mitigation or avoidance through various measures. The exploitation of opportunities is concerned with acquiring and employing resources in the space to gain certain advantages. Likewise, with risks, entrepreneurs perceive the risks and work towards the mitigation or avoidance of the perceived risk in the venture pathways. In this paper, entrepreneurship is viewed through the structuration and complexity science lens to present the entrepreneurial venture as the instantiated outcome of the entrepreneur–opportunity interaction through time and space. Complexity science offers a theoretical lens for exploring the complex interdependencies of a complex, and adaptive pluralistic world with irreversibility and randomness being the rules- dynamical systems in the natural and physical worlds. The key central concept of complexity is that interactivities between parts of open systems that creates unpredictable and seemingly random patterns. While the history of the open system is relevant in understanding its dynamics, the specific isolation of individual parts of the system does not reveal the system's casual mechanisms. The paper explores whether how entrepreneurial energy arises from the convergence/ collision of entrepreneurs with opportunities in a dynamical, unpredictable and random way in a nexus in space. Research paper Keywords: Entrepreneurship; Risks; Opportunities; Complex science Reference to this paper should be made as follows: Leong, D. (2020). Entrepreneurial Energy and Opportunities Existing in Space, Journal of Entrepreneurship, Business and Economics , 8 (2), 196–218. Preprint available at : https://doi.org/10.31124/ advance.13363433.v1